(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This scientific in the article nitrate ammonium work release raw materials, ammonium nitrate liquefaction harvest to do and how by doing nitrate ammonium liquefaction and glucanate addition based on stabilized with ammonia saltpeter get technology about data given.